Inconsistent Bodily Feedback? Interoceptive Sensibility Affects Internet Gaming Disorder in Emerging Adults - Zhouchao Lv; Cuijing Li; Jiamiao Zhang; Jinbo He (Behavioral Sciences, 2025)
Internet gaming disorder (IGD) has been a prominent social problem throughout the world, causing various physical health issues, and interoceptive sensibility—the ability to perceive internal bodily signals—may be a key factor in this process. However, the relationship between interoceptive sensibility and IGD remains unclear. This study examined how interoceptive sensibility contributes to IGD, the potential mediating roles of positive outcome expectancy and flow experience, as well as the moderating role of refusal self-efficacy. The serial mediation and moderated mediation analyses of data collected from 1733 students (1031 males and 702 females, Mage = 19.56) revealed that interoceptive sensibility was positively associated with IGD, and this connection was serially mediated by positive outcome expectancy and flow experience. Moreover, refusal self-efficacy buffered the positive association between positive outcome expectancy and IGD and between flow experience and IGD. These findings suggest that interoceptive sensibility plays a crucial role in the occurrence of IGD, highlighting the importance of addressing bodily awareness in prevention and intervention strategies. Additionally, enhancing refusal self-efficacy may help mitigate the negative effects of positive outcome expectancy and flow experience, offering potential avenues for reducing IGD risk.